Microbend fiber optic sensor for perioperative pediatric vital signs monitoring - Chen, Zhihao (2018)
We have demonstrated a highly sensitive microbend fiber optic sensor for perioperative pediatric vital signs monitoring that is free from direct contact with skin, cableless, electromagnetic interference free and low cost. The feasibility of our device was studied on infants undergoing surgery and 10 participants ranging from one month to 12 months were enrolled. The sensor was placed under a barrier sheet on the operating table. All patients received standard intraoperative monitoring. The results showed good agreement in heart rate and respiratory rate between our device and the standard physiological monitoring when signals are clean.